The Activation of Plasma Factor XIII with the Snake Venom Enzymes Ancrod and Batroxobin Marajoensis - Walter, M; Nyman, D; Krajnc, V; Duckert, F (Thrombosis and Haemostasis, 1977)
The snake venom enzymes Ancrod and Batroxobin marajoensis are able to activate human plasma factor XIII as shown by the formation of the γ-dimers. The concentration of γ-dimers increases with the concentration of the activating enzymes. Factor XIII activated by Ancrod or Batroxobin marajoensis is, however, unable to catalyse the incorporation of the amine dansylcadaverine into casein. The partially activated factor XIII is therefore not demonstrable by means of the artificial test system. This factor XIII loses little activity and remains activable by thrombin.